Association between wildfire smoke exposure and Seattle, Washington Pediatric Hospital services, 2006-2020 - Daaniya Iyaz; Alexandra Perkins; Jonathan D Cogen; Annie Doubleday; Coralynn Sack; Tania Busch Isaksen (IOP Publishing, 2023)
Pacific Northwest wildfire smoke events have been increasing in prevalence and severity over the past three decades, resulting in documented negative health outcomes in adults. However, there is less evidence demonstrating the effect of wildfire smoke in pediatric populations. To evaluate the association between wildfire smoke exposure and healthcare utilization in a pediatric tertiary medical center in Seattle, WA. We utilized a case-crossover study to determine the odds of pediatric emergency department (ED) visit/ hospital admission at Seattle Children's Hospital on wildfire smoke days versus non-wildfire smoke days during wildfire season (June to September), 2006-2020. The health outcomes dataset reports hospital encounters in two categories: ED visits or admissions that are for inpatient or observational purposes. The health outcomes dataset reports hospital encounters in two categories: ED visits or admissions that are for inpatient or observational purposes. The reported encounter types are mutually exclusive. We stratified analyses by individual-level characteristics and examined associations for lagged exposures 0-7 d prior to admission. In adjusted analyses, smoke exposure was associated with a 7.0% (95% CI: 3.0%-12.0%) increase in odds of all-cause hospital admissions and a 0.0% (95% CI: −3.0%, 3.0%) change in odds of all-cause ED visits. We also observed increases in the odds of all-cause hospital admissions ranging from 4.0% to 8.0%, for lagged exposure on days 1-7. When stratified by health outcomes, we found a 9.0% (95% CI: 1.0%-17.0%) and an 11.0% (95% CI:1.0%-21.0%) increase in the odds of ED visits for respiratory and respiratory infection-related concerns, respectively. Our results demonstrate associations between wildfire smoke and negative health effects in children. Similar to other studies, we found that wildfire smoke exposure was associated with an increase in respiratory-related ED visits and all-cause hospital admissions in a pediatric population. These results will help inform patient education and motivate interventions to reduce pediatric morbidity during wildfire season.